(untitled) (TEL Tempo, Espaço e Linguagem, 2026)
This study presents a historical and critical analysis of the constitution of early childhood education in Brazil, focusing on the intersection between public policies, medical-hygienist practices, and state guardianship of poor children between the late 19th and early 20th centuries. The qualitative research, grounded in a literature review, engages with authors such as Kuhlmann Junior, Rizzini, Gondra, Priore, and Marcílio, among others, to understand how hygienist discourse and European deterministic theories contributed to the medicalization and moralization of childhood. It is evident that assistance to "disadvantaged" children, legitimized by philanthropy and social medicine, functioned as an instrument of control and discipline of the subordinate classes, reinforcing social hierarchies and the hegemony of urban elites. The analysis also reveals that early childhood education emerged not only as a pedagogical and care space but also as an instance of social regulation, anchored in the ideals of progress and civilization inherent in Brazilian republican modernity.